Towards the Coupling Coordination Relationship between Economic Growth Quality and Environmental Regulation: An Empirical Case Study of China - Huan Huang; Fan Wang; Yi Xiao; Jiaxin Kuang (Discrete Dynamics in Nature and Society)
With the deterioration of the global climate, there is consensus that the environment and economy must develop in coordination. Effective environmental regulation (ER) is an important incentive of environmental protection, and there is a clear interaction mechanism between it and the economic growth quality (EGQ). In order to explore the intrinsic link between ER and EGQ, this study establishes a comprehensive evaluation index system from the research perspective of the coupling coordination degree (CCD). Based on the panel data of 30 provincial administrative regions in mainland China (excluding Tibet), from 2004 to 2017, the entropy method, coupling coordination model, and spatial econometric model are used to explore the CCD and the factors influencing the CCD of ER and EGQ. The key findings of this study were as follows: (1) The CCD of ER and EGQ system showed an upward trend in the fluctuation from 2004 to 2017. (2) In 2017, Beijing showed good coordination, Yunnan and Qinghai showed primary coordination, and the rest of the provinces showed moderate coordination. (3) The CCD of different regions in China is uneven. (4) Per capita GDP, per capita FDI, ER intensity, and industrial structure adjustment have promoting effects on the CCD, while per capita investment in fixed assets and environmental pressure have inhibiting effects on the CCD. Our conclusions are significant for promoting the integrated development of regional economy and ecological civilization, and provide a theoretical reference for other countries and regions to explore the relationship between ER and EGQ.